ON THE ARTICLE «GEOLOGICAL CONSEQUENCES OF AMORPHIZATION OF THE LITHOSPHERE AND UPPER MANTLE STRUCTURES CAUSED BY HYDROGEN DEGASSING» BY I. L. GUFELD - Alexey V. Nikolaev (Геодинамика и тектонофизика)
The commentary discusses possible directions for further research on the complex of issues arising in the analysis of the interaction of ascending hydrogen flows with the solid phase of the lithosphere and upper mantle.